2012
DOI: 10.1111/j.1442-200x.2012.03607.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of herniotomy in premature infants: Recent 10 year experience

Abstract: Although no predictive factor for complications was identified, there were some anesthetic and surgical complications in premature infants. If there is no risk of incarceration, herniotomy in premature infants should be performed at a time when the risk of anesthetic complications is decreased. If there is a risk of incarcerated hernia, herniotomy should be performed carefully in order to avoid occurrence of anesthetic and surgical complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…[ 3 ] Delaying HR until the infant is clinically stable for discharge allows for these medical conditions to be stabilized or resolved. [ 4 5 ] In this study, 79% of premature infants with inguinal hernia in the NICU had repair just before discharge. At repair, the mean PCA and mean body weight were 39.5 weeks and 2214 g, respectively.…”
Section: Discussionmentioning
confidence: 87%
“…[ 3 ] Delaying HR until the infant is clinically stable for discharge allows for these medical conditions to be stabilized or resolved. [ 4 5 ] In this study, 79% of premature infants with inguinal hernia in the NICU had repair just before discharge. At repair, the mean PCA and mean body weight were 39.5 weeks and 2214 g, respectively.…”
Section: Discussionmentioning
confidence: 87%
“…reported a recurrence rate of 2.6% (5/192) in VLBWI operated on at 28 weeks postnatally (20 month follow‐up). In contrast, Takahashi et al . noted no recurrence in 47 premature infants with BW < 2000 g (mean PCA and weight at surgery, 47.0 weeks and 4087 g, respectively; mean follow up, 31.2 months).…”
Section: Discussionmentioning
confidence: 90%
“…In contrast, Gonzalez Santacruz et al . (mean postnatal age and median weight at surgery, 40.55 days and 2585 g, respectively; mean follow up, 33.45 months) and Takahashi et al . detected no cases of testicular atrophy in their follow‐up periods.…”
Section: Discussionmentioning
confidence: 91%
“…They are reported to occur with a frequency from 6% to more than 10% and include bleeding, wound infection, recurrence, postoperative persistent hydrocele, testicular ascent, and testicular atrophy. [28][29][30] These complications have a threefold higher incidence when compared with older children. A retrospective analysis by Baird et al confirmed a higher rate of complications in infants aged less than 43 weeks of postconceptual age at surgery.…”
Section: Surgical Treatment General Considerationsmentioning
confidence: 99%
“…35 As indicated previously, the risk of complication can be as high as 10%, with testicular atrophy being reported with a frequency ranging from 1 to 10%. 6,[28][29][30] Open Repair and Diagnostic Laparoscopy Minimally invasive surgery is becoming increasingly popular even for newborns and preterms. Since the late 1990s, laparoscopy was used for diagnostic purposes to check the other side of the groin to prevent the risk for metachronous hernias.…”
Section: Available Surgical Techniquesmentioning
confidence: 99%